Health Related Quality of Life, Anxiety and Depression among Tuberculosis Patients in Kathmandu, Nepal - Devkota, Janardan; Devkota, Narmada; Lohani, Shyam Prasad (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: Tuberculosis remains one of the major public health problems in Nepal. This study was carried out to assess the Health related Quality of life and Anxiety- Depression level of Tuberculosis patients in Kathmandu. Material and Methods: A cross-sectional study was conducted at Urban Direct Observation Treatment Short Course center using 150 study populations. Questionnaires containing socio-demographic characteristics, Self Reporting Questionnaire, Short Forms Health Survey, Hamilton Anxiety Rating Scale, and Hamilton Depression Rating Scale. SPSS 20, SF-36 Scoring Software were used for data management. Results: Majority of respondents (57.3%) were male, age group of 21-25 years. Majority of respondents suffered from Extra Pulmonary Tuberculosis, gland TB was in higher prevalence (31.3%). Most of the respondents found to poor HRQoL score where only 1.4% female and 1.7% male’s had above average HRQoL. There was no correlation between anxiety, depression, Mental Component Summary and Physical Component Summary score in pulmonary Tuberculosis patients unlike Extra pulmonary Tuberculosis patients, where there was strong correlation between anxiety and depression (r=0.721, p=0.000). There was negative correlation between PCS and MCS (r= -0.232, p= 0.037). There was no association between gender and PCS score on both types of TB patients. At majority of domain of HRQoL male had higher score than female. Conclusion: Co-morbidities of anxiety and depression in tuberculosis patients impact on health-related quality of life. Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (1): 13-18